Factors Affecting The Efficiency of Nurses Performance Using The Team Nursing Method in Hospitals: Systematic Literature Review - Jesica Catleya Hadi; Iyos Sutresna; Heri Ridwan (INDOGENIUS, 2026)
Background & Objective: Nurses’ performance efficiency plays a crucial role in supporting the quality of hospital services. One nursing care delivery method considered effective in improving nurses’ performance efficiency is the team nursing method, which emphasizes task distribution, coordination, and collaboration among nursing team members. This study aimed to identify the relationship between the implementation of the team nursing method and nurses’ performance efficiency in hospitals. Method: This study employed a systematic literature review design with a scoping review approach. The reviewed articles were published between 2021 and 2025 and were obtained from the Google Scholar, ScienceDirect, Cochrane, PubMed, and Springer databases. Article selection was conducted using the PICOS framework, while the quality of the articles was assessed using the JBI Critical Appraisal Tools. Result: The results of the literature review indicate that the implementation of the team nursing method contributes positively to improving nurses’ performance efficiency through effective communication, good coordination, and strong support from hospital management. Conclusion: The team nursing method can be recommended as a nursing management strategy to enhance nurses’ productivity and the quality of hospital services.